Influence of four wave mixing on modulation format performance under 100 Gb/s data rate - Haider Jabber, Abed; Norashidah, Md. Din, Assoc. Prof. Ir. Dr.; Mohammed Hayder, Al-Mansoori, Dr.; Fairuz, Abdullah, Dr.; Hilal Adnan, Fadhil, Dr.; Noora, Salim; Adnan, Saher (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/